2019
DOI: 10.1097/yct.0000000000000598
|View full text |Cite
|
Sign up to set email alerts
|

Lifesaving Electroconvulsive Therapy for a Child With Autism Spectrum Disorder, Severe Self-Injurious Behavior, and Neuroleptic Malignant Syndrome

Abstract: We present a case of a preteen with autism spectrum disorder and severe self-injurious behavior who developed neuroleptic malignant syndrome on antipsychotics and required urgent electroconvulsive therapy and continued maintenance electroconvulsive therapy for ongoing clinical stability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…66 Electroconvulsive therapy may also be effective in self-injurious behavior along the agitated catatonia spectrum and in self-injurious behavior and NMS. 70,71,123,124 One study found that self-injurious behavior in female patients was associated with poor outcome to ECT. 72…”
Section: Evidence For Ect In Self-injurious Behavior and Aggressionmentioning
confidence: 99%
“…66 Electroconvulsive therapy may also be effective in self-injurious behavior along the agitated catatonia spectrum and in self-injurious behavior and NMS. 70,71,123,124 One study found that self-injurious behavior in female patients was associated with poor outcome to ECT. 72…”
Section: Evidence For Ect In Self-injurious Behavior and Aggressionmentioning
confidence: 99%
“…Clinical trials have proved that transcranial direct current stimulation (tDCS), 1 deep brain stimulation (DBS), 2 and electroconvulsive therapy (ECT) 3 have shown potency in neurology and psychiatry. More specifically, these therapies have been used clinically to treat cerebral ischemic diseases (epilepsy 4 and stroke 5 ), neurodegenerative diseases (Parkinson's syndrome 6 ), and genetic disorders (depression 7 and autism 8 ). However, most previous studies focused on observing changes in patients' physiological functions; they ignored the alteration of the mechanical properties and microscopic structure/compositions of the brain under local electric fields, even reports on this subject regarding ex vivo experiments.…”
Section: Introductionmentioning
confidence: 99%
“…In patients with neuroleptic malignant syndrome, electroconvulsive therapy (ECT) helps with the alteration of temperature and level of consciousness. ECT should be considered in patients not responding to medical therapy in the first week, those in whom residual catatonia persists after other symptoms have resolved, and those in whom lethal catatonia is suspected as an alternative or concomitant disorder [32,33,36,37,38]. In a case series study of 15 patients who had neurocognitive or schizophrenia spectrum disorders and developed NMS after exposure to multiple antipsychotic drugs.…”
Section: The Role Of Electroconvulsive Therapy In Nmsmentioning
confidence: 99%
“…ECT is generally safe, however, serious treatment-related complications including cardiac arrest and ventricular fibrillation have been reported [32][33][34][35][36][37][38].…”
Section: The Role Of Electroconvulsive Therapy In Nmsmentioning
confidence: 99%